PATTERNS OF EXTENSION, INCENTIVES, LEADERSHIP STYLES, AND THEIR EFFECT ON EMPLOYEE PERFORMANCE - Sonang Sitohang (Bajang Institute, 2021)
This paper aims to explain the effect of counseling patterns, incentives and leadership styles on the performance of the brown sugar micro-small industry Clushter in Blitar Regency. The results of the preliminary research show that the problems at this Clushter are the low performance of employees, the pattern of counseling given by the technical coach tends to be generalized, and the provision of incentives is less transparent. There has been no integration between leadership styles and individual abilities of employees which include talents, interests, and personality, skills of employees so that they have not been able to improve employee performance. The research model with hypothesis development was derived based on the literature. To provide empirical evidence, this study conducted a survey, primary data was collected using a list of questionnaires, and saturated sampling of 33 employees. The results showed that the pattern of counseling, incentives and leadership styles had a direct positive and significant effect on employee performance. The implication of the research is to examine the perceptions of 33 employees at the Clushter for Micro Small Brown Sugar Industry in Blitar Regency. The analytical technique used is multiple linear regression. This paper contributes to the theory of organizational behavior by explaining the effect of counseling patterns, incentives and leadership styles on employee performance.